Copper(II) removal from aqueous solutions by fly ash - Panday K.K.; Prasad G.; Singh V.N. (My University, 2025)
The removal of Cu(II) by adsorption on fly ash has been found to be concentration, pH and temperature dependent. The kinetics of adsorption indicates the process to be diffusion controlled. The Langmuir constants have been calculated at different temperatures, and the adsorption has been found to be endothermic (ΔH = 15.652 kcal mol-1). The maximum removal is observed at pH 8.0, and variation in adsorption with pH has been explained on the basis of surface ionisation and complexation. © 1985.